A Comparative Study on Biological Removal of Cr(VI) by Fusarium Solani under Different Modes of Operational Strategies - Sen, Mousumi; Dastidar, Manisha Ghosh; Roychoudhury, Pradip K. (International Journal of Engineering and Technology Innovation, 2014)
In the present work biological removal of Cr(VI) was carried out in fed batch mode of operation using the growing cells of Fusarium solani isolated from soil. The fed batch process was studied by constant volume pulse feeding (CVPF) and increasing volume pulse feeding (IVPF), and the effects of these operational strategies on biological performance were compared with a conventional batch process. Batch studies indicated the maximum specific Cr(VI) removal to be 71 mg/g at pH 5.0 and at 500 mg/l initial Cr(VI) ion concentration. In CVPF process the maximum specific Cr(VI) removal was found to be 35.51 mg/g and 25.15 mg/g as compared to 51.9 mg/g and 42.5 mg/g obtained in IVPF during first and second pulse feedings respectively in both the cases. These results were compared with the Cr(VI) removal obtained in earlier studies conducted by the present authors using the continuous mode of operation. The continuous mode of operation was found to be the best operational strategy in which the process could be operated for longer duration with maximum specific Cr(VI) removal of 62.27 mg/g. Nearly complete removal was obtained using single stage reactor at lower Cr(VI) concentrations up to 100 mg/l and a multi stage reactor at higher Cr(VI) concentration.